Sign-Changing Solutions for Discrete Second-Order Three-Point Boundary Value Problems - Tieshan He; Wei Yang; Fengjian Yang (Discrete Dynamics in Nature and Society)
We consider the second-order three-point discrete boundary value problem. By using the topological degree theory and the fixed point index theory, we provide sufficient conditions for the existence of sign-changing solutions, positive solutions, and negative solutions. As an application, an example is given to demonstrate our main results.